(untitled) (The Mega Journal, 2023)
This paper explores artist Pushpa Kumari’s female-centered perspectives in Mithila Paintings that foreground the grace of Shakti, goddess Kali, in all females. Moreover, it examines the agency of women as a source of fertility and energy centralizing on how the bi-union of Prakriti and Purusha, the cosmicized versions of the earthly phenomenal male and female, reflects one integrated form, an indivisible whole. Basically, the paper is based on Kumari’s preference for tantrism, which accepts fundamental dualism, through which an individual encounters universal phenomena. Thus, this paper will provide a new insight on females’ subjectivity—how in tantric rituals every woman, a counterpart of feminine principle, as a microcosmic version of feminine power shakti becomes a reincarnation of cosmic energy symbolizing the ultimate essence of reality.